Is the spell really broken? Bio-psychological explanations of religion and theistic belief - Barrett, J (Taylor and Francis, 2007)
Recent advances in the evolutionary and cognitive sciences of religion have raised questions about whether the assumptions and findings of these fields as applied to religion conflict with belief in gods. Specifically, three scientific approaches to religion (Neurotheology, Group Selection, and Cognitive Science of Religion) are sketched, and five arguments against theistic belief arising from these approaches are discussed and evaluated. None of the five arguments prove formidable challenges for belief in gods.